DESKRIPSI KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL MATERI POLA BILANGAN KELAS VIII SMP NEGERI 4 SUNGAI RAYA - Muhammad Zaki; Muhammad Rif’at; Halini Halini (Universitas Tanjungpura, 2021)
AbstractThis research aims to describe the ability of mathematical reasoning students in solvingnumber pattern material problems in class VIII SMP Negeri 4 Sungai Raya. The researchmethod used in this research is descriptive. The subjects in this study were 32 students. Thedata collection tools used are tests and interviews. Based on the test results, it shows thatthe students' mathematical reasoning ability in a different category seen from eachindicator. The ability to make assumptions, students being in the high category, meaningthat they are able to write down the next number from the given number pattern. Theability to provide an explanation of the existing pattern is in the medium category meansthat students only write calculations but do not write down explanation of the process offorming the pattern in the picture. The ability to make the conclusion from the statement,students are in the medium category, meaning that students do not draw conclusionscorrectly just do the calculations alone. The ability to use patterns to analyze mathematicalsituations, students are in the low category means that students have not been able tomention and write a pattern formed from an array of picture.Keywords : Mathematical Reasoning Ability, Number Pattern, Solve The Problem